2003
DOI: 10.1034/j.1399-0004.2003.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of gap‐ and tight‐junction mutations in Turkish families with autosomal‐recessive non‐syndromic hearing loss

Abstract: Mutations in genes encoding gap- and tight-junction proteins have been shown to cause distinct forms of hearing loss. We have now determined the GJB2[connexin 26 (Cx26)] mutation spectrum in 60 index patients from mostly large Turkish families with autosomal-recessive inherited non-syndromic sensorineural hearing loss (NSSHL). GJB2 mutations were found in 31.7% of the families, and the GJB2-35delG mutation accounted for 73.6% of all GJB2 mutations. The carrier frequency of GJB2-35delG in the normal Turkish pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
52
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 34 publications
13
52
3
1
Order By: Relevance
“…Aspartic acid is predicted to disrupt the hydrophobicity of the region, as well as the predicted α and β regions in transmembrane domain 2 (Kyte and Doolittle, 1982). The prevalence of these mutations in different populations is not universal; for example, no disease-associated mutations in claudin-14 have been found in Turkish patients with deafness (Uyguner et al, 2003). Nevertheless, recently, Ben-Yosef et al reported that claudin-14-null mice have a normal endocochlear potential but are deaf owing to rapid degeneration of cochlear outer hair cells, followed by slower degeneration of the inner hair cells (Ben-Yosef et al, 2003), which supports a role of claudin-14 in hearing.…”
Section: Claudin Genes and Claudin Gene Expressionmentioning
confidence: 99%
“…Aspartic acid is predicted to disrupt the hydrophobicity of the region, as well as the predicted α and β regions in transmembrane domain 2 (Kyte and Doolittle, 1982). The prevalence of these mutations in different populations is not universal; for example, no disease-associated mutations in claudin-14 have been found in Turkish patients with deafness (Uyguner et al, 2003). Nevertheless, recently, Ben-Yosef et al reported that claudin-14-null mice have a normal endocochlear potential but are deaf owing to rapid degeneration of cochlear outer hair cells, followed by slower degeneration of the inner hair cells (Ben-Yosef et al, 2003), which supports a role of claudin-14 in hearing.…”
Section: Claudin Genes and Claudin Gene Expressionmentioning
confidence: 99%
“…Thus, a stop When considered by country, the carrier frequency of this mutation is 3.4% in Italy, 3.5% in Greece, 2.75% in France, and 2.8% in Malta and Portugal, whereas it shows a marked decrease in countries in America and Asia (16). The carrier frequency in Turkey has been reported to range between 1.17% and 1.78% in different studies (17,18). In other studies conducted in Turkey, the c.35delG mutation has been found in 5-53% of individuals with hearing impairment (7,10).…”
Section: Discussionmentioning
confidence: 99%
“…When the 35delG mutation of the GJB2 gene is mutant in both alleles, it causes SNHL. In NSSNHL patients with familial autosomal recessive inheritance, the rate of 35delG homozygosity was reported as 17.5%-21.7%, and the rate of heterozygous mutation was reported as 1.9%-4.3% (18,25,26). Regarding the familial history of patients in the study group of our study, congenital NSSNHL was determined at least in one person in the families of 18.3% of patients.…”
Section: Discussionmentioning
confidence: 99%